Public Access to Information for Development : A Guide to the Effective Implementation of Right to Information Laws - Lemieux, Victoria L. (Washington, DC: World Bank, 2016)
With more than 100 right to information (RTI) laws—also called freedom of information or access to information laws—now in place globally, the groundwork has been laid to advance more transparent, accountable, and inclusive governance as a pathway to poverty reduction and economic development. This guide explores the historical development of RTI laws, the factors that drive passage and effective implementation of these laws, the operation of the laws, and the impact of these laws in different country contexts and sectors, as well as the challenges of measuring the contribution of RTI laws to development outcomes.